2014
DOI: 10.1097/qco.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Echinocandin resistance

Abstract: Purpose of review Echinocandin resistance in Candida is a great concern, as the echinocandin drugs are recommended as 1st line therapy for patients with invasive candidiasis. Here we review recent advances in our understanding of the epidemiology, underlying mechanisms, methods for detection and clinical implications. Recent findings Echinocandin resistance has emerged over the recent years. It has been found in most clinically relevant Candida species, but is most common in C. glabrata with rates exceeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
143
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 260 publications
(154 citation statements)
references
References 56 publications
6
143
1
4
Order By: Relevance
“…While drug resistance has emerged with echinocandins over the last decade (Arendrup and Perlin, 2014), strategies to efficiently suppress the acquisition of resistance have not been successfully established. A key consideration to this dilemma is that it lacks proper measures of how to overcome development of resistant mutant subpopulations with antifungal drugs.…”
Section: Discussionmentioning
confidence: 99%
“…While drug resistance has emerged with echinocandins over the last decade (Arendrup and Perlin, 2014), strategies to efficiently suppress the acquisition of resistance have not been successfully established. A key consideration to this dilemma is that it lacks proper measures of how to overcome development of resistant mutant subpopulations with antifungal drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of non-albicans Candida spp., particularly C. glabrata, and antifungal resistance have been increasing over time (16)(17)(18). The occurrence of resistant yeasts, including multidrug-resistant strains (19), renders the rapid identification and susceptibility testing of fungi isolated from blood essential (17). The availability of colonies on agar is a requirement for definitive testing.…”
Section: Resultsmentioning
confidence: 99%
“…While a Gram stain indicating yeast cells provides important information for the initiation of antifungal therapy, species identification and AST results are critical for the administration of appropriate targeted treatment (15). The prevalence of non-albicans Candida spp., particularly C. glabrata, and antifungal resistance have been increasing over time (16)(17)(18). The occurrence of resistant yeasts, including multidrug-resistant strains (19), renders the rapid identification and susceptibility testing of fungi isolated from blood essential (17).…”
Section: Resultsmentioning
confidence: 99%
“…The goal of current echinocandin breakpoints is to distinguish C. glabrata isolates with a WT FKS from those containing FKS mutations that are unlikely to respond to echinocandin therapy (9). While mutations at almost every amino acid position within the FKS hot spot 1 and 2 regions confer some degree of resistance (20), recent studies have shown that the majority of mutations that affect C. glabrata susceptibility to the echinocandins are located within FKS1 and FKS2 HS1 regions. Accordingly, these regions are the primary targets for molecular assays to detect drug resistance (6,21).…”
Section: Discussionmentioning
confidence: 99%